Evaluation of care for at-risk newborns from the perspective of a public health policy - Luque, Ana Lúcia Forti; de Lima, Célia Mara Garcia; de Barros Leite Carvalhaes, Maria Antonieta [UNESP]; Tonete, Vera Lúcia Pamplona [UNESP]; de Lima Parada, Cristina Maria Garcia [UNESP] (FapUNIFESP (SciELO), 2011)
The aim was to evaluate the care for at-risk newborns under follow-up in their first year of life by the Growing Happily Program, developed in a city in inner São Paulo state. It is a population-based epidemiological health program evaluation study, which was based on the national guidelines of the Agenda of Commitments to Children and Child Mortality Reduction for data analysis. Results showed the program's institutional vulnerability, caused by problems related to its structure and process, with implications for its outcomes. Considering the adaptation of the criteria adopted by the Program for defining at-risk newborns, as well as the proposed interventions and strategies, in consonance with the Agenda of Commitments, the need for managers to make it a priority is appointed, by effectively including it in public health care policies to be developed in cities, in order to reverse the institutional vulnerability identified.
Avaliação da atenção ao recém-nascido de risco, na perspectiva de uma política pública de saúde
Keywords: Health Services Evaluation; Infant; Newborn; Risk Groups; Vulnerability